Design and preparation of antibacterial coatings on biodegradable polylactic acid-based medical implants - Jiao Pan; Kejiang Li; Chuan Li; Zhihao Wang; Hongxin Shi; Dengbang Jiang; Hongli Li; Minglong Yuan (Materials & Design, 2025)
Implant-associated infections (IAIs) pose significant challenges to medical implants, especially in orthopedics, due to bacterial biofilm formation and increasing antibiotic resistance. Polylactic acid (PLA), a biodegradable material, is commonly used in implants but lacks inherent antibacterial properties. This study presents a novel multilayer antibacterial coating for PLA using dopamine (DA) self-polymerization and layer-by-layer (LBL) assembly. The PLA surface was first modified with polydopamine (pDA) coating. Antimicrobial peptides (AMP) were then covalently grafted onto the pDA-functionalized PLA surface through Michael addition and Schiff base reactions. Subsequently, a multilayered coating was constructed via electrostatic adsorption with hyaluronic acid (HA). The coating significantly enhanced the hydrophilicity of PLA and released AMP continuously for over 15 days, exhibiting > 99 % antibacterial efficacy against Staphylococcus aureus. Scanning electron microscopy (SEM) and biocompatibility assessments indicate that the coating exhibits both effective antibacterial properties by inhibiting bacterial adhesion and disrupting the integrity of the bacterial cell membrane, and demonstrates excellent biocompatibility. Besides, in the implant model of subcutaneous infection, the coating showed ability of better anti-infection and lower inflammatory response. The present study develops an antibacterial coating technology designed for biodegradable PLA implants, demonstrating significant potential to enhance the prevention and treatment of implant-associated infections.